Aspects of balance between the legislative and executive powers in the Iraqi constitution. Lecturer - Shakir Abd, Dr. Abu Thar (The college of law and political science journal, 2023)
The principle of separation of powers is one of the principles on which Westerndemocratic philosophy is based, in an attempt to limit individual power, or preventthe domination of an authority over other authorities. At the same time, thisprinciple is one of the complements of the principle of people’s sovereignty. In Iraq,a representative republic (parliamentary) is democratic, based on the principle ofseparation of powers.The balance between the legislative and executive authorities will not beachieved on the ground by simply claiming that this balance exists. Rather, thisbalance must be strengthened legally and legally. Therefore, we decided to showthe extent of the balance between the legislative and executive authorities in Iraq,the nature and reality of this balance, and knowing the seriousness of the means ofparliamentary oversight. Over the work of the executive authority, and to indicatethe means of the executive authority’s control over the legislative authority.